PEMBERIAN KOMPRES HANGAT WWZ (Warm Water Zack) PADA PASIEN INFEKSI SALURAN KEMIH (ISK) DENGAN MASALAH NYERI AKUT - Khalis, Naila; Sapuri, Dahlia; Batubara, Khairunnisa (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Urinary Tract Infection (UTI) occurs due to infection that occurs in the upper and lower urinary tract, where the presence of bacteria ranges from around 10.5 colonies per milliliter (CFU/ml) in a urine sample. To treat the main complaint in the form of pain, nurses can intervene with pharmacological therapy in the form of antibiotics and non-pharmacological therapy such as warm compresses to relieve pain, namely by applying warm compresses to the painful area. The purpose of writing this scientific paper is so that researchers can provide health education to patients and carry out nursing care for patients suffering from UTI with complaints of acute pain at the Kisaran City Hospital. This study uses a descriptive approach in the form of a case study. The results showed that giving warm compresses using WWZ (warm water zack) or better known as hot bubbles to the patient's painful area was proven to be able to reduce pain levels. In client 1, the pain that was initially on a scale of 6-7 decreased to 3-4, while for client 2, the pain level that was initially on a scale of 5-6 decreased to 2-3. The identified nursing diagnosis is acute pain related to physiological injury, indicated by pain during urination. The conclusion is that giving warm compresses is one of the effective non-pharmacological methods to reduce the pain felt by clients suffering from Urinary Tract Infection.